How Is Connectedness With Nature Linked to Life Satisfaction or Depression Among Chinese People Living in Rural Low-Income Households? A Serial Mediation Model - Yang, Chunyu; Chen, Xiaoyan; Yao, Jun; An, Jing (Frontiers in Public Health, 2022)
Objectives A serial multiple mediation model is tested in this study to investigate the potential sequentially mediating effect of affect balance and social cohesion in the association between connectedness to nature and psychological adjustment. Methods A total of 675 Chinese people living in rural low-income households from Jiangsu province participated in the study. Connectedness to Nature Scale (CNS), Positive Affect and Negative Affect Scale (PANAS), Social cohesion scale (SCS), Satisfaction with Life Scale (SWLS) and Patient Health Questionnaires (PHQ9) were measured in this paper. Results Results indicated that the serial multiple mediation of affect balance and social cohesion in the association between connectedness to nature and life satisfaction was significant among the full-size sample, the adult-report and the old people report, but this effect is relatively small. Specifically, the serial mediation accounting for 2.01%, 1.69% ,2.67% of the total effect explained by connectedness to nature on life satisfaction, while 2.66%, 2.35%, 2.91% of the total effect explained by connectedness to nature on depression among full sample size, adults, and old people, respectively. In addition, the findings corroborate the important roles of affect balance and social cohesion in activating connectedness to nature. Conclusions We discussed the possible ways to enhance the life satisfaction and decrease depression for Chinese people living in rural low-income households and the limitations of this study. To our knowledge, this is the first study to investigate the relationship between connectedness to nature and psychological adjustment in terms of affect balance and social cohesion, more mechanisms through connectedness to nature and psychological adjustment could be considered in future study.